(untitled) (مجلة المنصور, 2023)
This study was carried out to study the effect of Entamoeba histolytica infection and its impact on some blood parameter such as hemoglobin, packed cell volume (p.c.v.), cholesterol and Triglyceride (TG) among 430 patients who attended AL-Furat AL-owset Teaching hospital in Kufa city / Iraq during six month period from March and September2018. Those patients suffered from diarrhea and abdominal discomfort. The frequency of Entamoeba histolytica occurring was (70) infection out of (430, 16.3%). Among those (70) infected there were male n=32/70,45.7%, while females represented n=38/70,54.3%. The result of this study showed no significant affect in cholesterol and Triglyceride but significant decrease in Hb and pcv in comparison with control group of (30) healthy individual which was included in this study.